2014
DOI: 10.1007/s12035-014-8821-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Neurogenes for Long-Term Spaceflight: Dopamine and Serotonin Brain System

Abstract: Mice were exposed to 1 month of spaceflight on Russian biosatellite BION-M1 to determine its effect on the expression of key genes in the brain dopamine (DA) and serotonin (5-HT) systems. Spaceflight decreased the expression of crucial genes involved in DA synthesis and degradation, as well as the D1 receptor. However, spaceflight failed to alter the expression of tryptophan hydroxylase-2, 5-HT transporter, 5-HT1A, and 5-HT3 receptor genes, though it reduced 5-HT2A receptor gene expression in the hypothalamus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…These results suggest that DS can inhibit the abnormal changes in many neurotransmitters and therefore prevent SLSE-impaired learning and memory. Previous studies revealed that hippocampal NE levels, cortical 5-HT levels, and DA system activity were decreased in space or simulated microgravity (Blanc et al, 1998; Liu et al, 2010; Popova et al, 2015). We identified novel changes in neurotransmitters in simulated spaceflight that need to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that DS can inhibit the abnormal changes in many neurotransmitters and therefore prevent SLSE-impaired learning and memory. Previous studies revealed that hippocampal NE levels, cortical 5-HT levels, and DA system activity were decreased in space or simulated microgravity (Blanc et al, 1998; Liu et al, 2010; Popova et al, 2015). We identified novel changes in neurotransmitters in simulated spaceflight that need to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that one-month spaceflight did not change BDNF gene expression in the brain regions including the frontal cortex, visual cortex, caudate putamen, hippocampus, hypothalamus and midbrain raphe nuclei [16]. The effects on 5-HT1AR, 5-HT2AR and 5-HT3R were also examined in the same spaceflight, and it was reported that the spaceflight decreased 5-HT2AR gene expression in the hypothalamus without any significant effects on the expression of 5-HT1AR, 5-HT2AR and 5-HT3R in other brain regions [17]. These effects were different from those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of brain-derived neurotrophic factor (BDNF) was not affected in the same condition [16]. Among monoaminergic systems, the expression of serotonin 2A receptor (5-HT2AR) and dopamine D1 receptor was reduced in the hypothalamus [17]. However, there are still limited studies on spaceflight and ground-based experiments that investigated gene expression of functional molecules in the brain under altered gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on findings from earlier animal studies related to spaceflight, it is hypothesized to find changes in humans as well. 30,100 Earth-based studies have shown that changes in neurotransmitters have major implications for attention, 101 (long-term) memory, 102 arousal 103 and motor activity. 104 Determining neurotransmitter and hormonal imbalance in space travelers is therefore important to get fundamental insight into how the central neural system adapt to microgravity and in addition, to get insight into the relation between these alterations and behavioral processes.…”
Section: Implications For Countermeasures and Neuroimaging In Spaceflmentioning
confidence: 99%